Microbial Keratinase: Next Generation Green Catalyst and Prospective Applications - Nnolim, Nonso E.; Udenigwe, Chibuike C.; Okoh, Anthony I.; Nwodo, Uchechukwu U. (Frontiers in Microbiology, 2020)
The search for novel renewable products over synthetics hallmarked this decade and those of the recent past. Most economies that are prospecting on biodiversity for improved bio-economy favor renewable resources over synthetics for the potential opportunity they hold. However, this field is still nascent as the bulk of the available resources are still non-renewable based. Microbial metabolites are viable alternative; nonetheless, vast microbial resources remain under-exploited thus, the need for a continuum in the search for new products, or bio-modifying existing products for novel functions through an efficient approach. Environmental distress syndrome has been identified as a factor that influences the emergence of genetic diversity in prokaryotes. Still, the process of how the change comes about is poorly understood. The emergence of new traits may present a high prospect for the industrially viable organism. Microbial enzymes have prominence in the bio-economic space and proteases account for about sixty per cent of all enzyme market. Microbial keratinases, which is the trust of the review, are proteases which are continuously gaining momentum in biotechnology owing to their effective bio-conversion of recalcitrant keratin-rich wastes generated from vast arrays of agro-industrial processing facilities. The robust and extreme catalytic properties of keratinases have increased their market demand as an alternative to conventional industrial dekeratinization processes and, this is with a view of achieving sustainable development. Keratinase-mediated biodegradation of keratinous materials has revitalised the prospects for the utilisation of cost-effective agro-industrial wastes, as readily available substrates, for the bio-production of high-value products. Here, an overview of microbial keratinase; sources and functional properties with considerable emphasis on catalytic tendency improvement were articulated. Keratinase applications and prospect high-end use including dehairing agent in leather processing and functional feed in animal husbandry were appraised.